(untitled) (Ameghiniana, 2023)
Recent fieldwork on Neogene deposits of northern Chile led to the discovery of new material, including three new species of the echinoid genus Arbacia: Arbacia quyllur sp. nov. from the Miocene, Arbacia terraeignotae sp. nov., and Arbacia larraini sp. nov. from the Pliocene. In the Pleistocene, the new material includes the first fossil occurrence of the extant species Arbacia spatuligera and new specimens of the extant species Tetrapygyus niger. The specimens and new species described here reveal the significant past diversity of the genus Arbacia and increase our knowledge of the overall diversity of the genus in South America, showing an older origin (upper Miocene) and higher species richness of the genus Arbacia along the Chilean coasts than previously thought.